Simulation of multiple pool fires involving two different fuels. (July 2017) - Vasanth, S.; Tauseef, S.M.; Abbasi, Tasneem; Abbasi, S.A.
Abstract: When two or more pool fires burn in close enough proximity to influence one another, the resultant combination is termed 'multiple pool fire' (MPF). Even though MPFs occur fairly often in chemical process industries, with highly destructive consequences, much lesser work has been done towards simulation, modeling, and control of MPFs than on stand-alone pool fires. Among the factors which strongly influence the interaction among the MPFs, and the consequent damage MPFs may cause, the most important is the type of fuel contained in the individual pools. This aspect affects the temperatures of the interacting flames, their soot production, and the resultant radiation load. However, studies to dynamically model this aspect have not been carried out so far. In this paper an attempt has been made, arguably the first of its kind, to explore the efficacy of computational fluid dynamics (CFD) in simulating the effect of fuel types on MPF clusters. A fair agreement has been found between the CFD simulation and the experimental findings reported by Vincent and Gollahalli (1995). The agreement between the experimental data and CFD simulation results is good considering the fact that the soot production has not been accounted by us. Highlights: Accidents involving multiple pool fires (MPFs) occur frequently in process industries. The fuel in the individual pools strongly influence the interaction among the MPFs. The efficacy of CFD in simulating the effect of fuel types on MPs is explored. CFD simulation was done without the soot production accounted for. Good agreement was found between the experimental data and CFD simulation results.